Comparing the Economic Performance of Two Rice Technologies in West Kano Irrigation Scheme, Kenya - Mwatete, G. K.; Sumukwo, J.; Kipkorir, E. C.; Kipkoech, A. K. (Africa Environmental Review Journal, 2017)
The contributions of rice in alleviating hunger and poverty among rural households in Kenya has led to the belief that better rice technologies can contribute in enhancing the role of rice in poverty reduction. It is for this reason that this study attempts to analyse the economic performance of rice technologies and their effects to rural households in West Kano Irrigation Scheme (WKIS) of Western Kenya. The study involved a survey of 123 households on their rice farming activities and field experimental trials on Conventional paddy and Systems of Rice Intensification (SRI) technologies. Conventional paddy system is a method of rice production where about 21 days or older seedlings are transplanted. Random planting and smaller spacing, usually 20cm by 15cm spacing or less is maintained, with 2 to 3 seedlings per hill, while on the other hand, SRI is rice production technology which involves transplanting 8-12 days old seedlings to the main field in order to maximize the tillering potential with single seedling per hill, with a wider spacing. Results of the study indicated that 89% of the households produced rice for both consumption and commercial purposes. Findings also indicated that the SRI system saved about 64% of water compared to the conventional paddy system. Experimental results showed that the yield difference between Conventional paddy method and SRI when 12 days old transplanted seedlings for SRI were compared with 21 days old seedlings for Conventional paddy system, the yields for IR2793 rice variety when SRI was used increased by up to 33.4 % compared to Conventional paddy method. In the case of basmati 370 rice variety, SRI increased grain yield of up to 53.3 % compared to Conventional paddy method. The study reveals that SRI method of rice production saves about 64% of water compared to the Conventional method. Furthermore, net revenue margins for SRI was higher by KSh. 58,275 (US 583) per acre of land. In conclusion, therefore, there is need to adopt the SRI method of spacing 25cm by 25 cm, since water is a very scarce commodity in the study area. Hence, adoption of this SRI method of rice production would be an important instrument for poverty reduction among the rural households of West Kano irrigation scheme and Kenya at large.